1999
DOI: 10.1103/physrevd.59.115009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anRRRRdimension 5 operator on proton decay in the minimal SU(5) SUGRA GUT model

Abstract: We reanalyze the proton decay in the minimal SU(5) SUGRA GUT model. Unlike previous analyses, we take into account a Higgsino dressing diagram of dimension 5 operator with right-handed matter fields (RRRR operator). It is shown that this diagram gives a dominant contribution for p → K + ν τ over that from LLLL operator, and decay rate of this mode can be comparable with that of p → K + ν µ which is dominated by the LLLL contribution. It is found that we cannot reduce both the decay rate of p → K + ν τ and that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
275
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(285 citation statements)
references
References 42 publications
10
275
0
Order By: Relevance
“…On the experimental side, the bounds coming from the SuperKamiokande experiment have reached τ (p → e + π 0 ) ≥ 5.3 × 10 33 yrs [7] and τ (p → K +ν ) ≥ 1.9 × 10 33 yrs [8]. On the theoretical side, these bounds have motivated new detailed studies of proton decay via dimension-5 operators in supersymmetric GUTs [9]- [14]. These analyses showed that the present bounds disfavour this class of models, although the theoretical predictions strongly depend on the flavour structure assumed [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the experimental side, the bounds coming from the SuperKamiokande experiment have reached τ (p → e + π 0 ) ≥ 5.3 × 10 33 yrs [7] and τ (p → K +ν ) ≥ 1.9 × 10 33 yrs [8]. On the theoretical side, these bounds have motivated new detailed studies of proton decay via dimension-5 operators in supersymmetric GUTs [9]- [14]. These analyses showed that the present bounds disfavour this class of models, although the theoretical predictions strongly depend on the flavour structure assumed [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…We do include the leading contributions from chargedhiggsino dressing. In the case of charged-lepton decay modes these contributions turn out to be negligible, but [23] has shown that they can be important for the antineutrino decay modes. The bulk of the contributions come from charged-wino dressing, though the neutralwino dressing can be comparable for the antineutrino decay modes.…”
Section: Nucleon Decay Computationsmentioning
confidence: 99%
“…L,R can be found in Table 1 of [23], given in terms of the coefficients of the various four-fermion operators generated by dressing of the superpotential operators shown in Eqn. (1).…”
Section: Nucleon Decay Computationsmentioning
confidence: 99%
See 2 more Smart Citations